Aplicación del Grade en las recomendaciones de meta-análisis en red en la guía Colombiana de falla cardíaca (2016)
ABSTRACT: The network meta-analysis (NMA) can incorporate and analyze indirect comparisons between interventions as an aid to the development of recommendations in clinical practice guidelines. The aim of this article is to summarize the literature review conducted by the group on NMA, GRADE recommendations and to evaluate how the recommendation for this question of the guideline was developed. Methodology: To the question about the use of beta-blockers (BB) in patients with heart failure stage C ACC/AHA, a systematic search was conducted. An NMA was found that summarized the findings of other studies; it was suitable to describe the application of GRADE criteria as an example in this type of studies. Results: The overall result of the meta-analysis showed a significant reduction in mortality with the use of BB against any comparator. All comparisons were indirect except the study of carvedilol with metoprolol tartrate. All BB showed reduced mortality, but no statistical significance when compared with each other. This NMA did not publish probability in the order of treatment. Analysis of the general characteristics of the studies included in the NMA did not showed intransitivity. For comparison between metoprolol and carvedilol it was seen that the effect of direct and indirect comparison was consistent. Conclusion: NMA are a way of summarizing the available evidence including indirect comparisons, they have a particular methodology and the criteria of the GRADE group are practical and applicable as was shown in the development of this clinical practice guideline.